2011
DOI: 10.4103/0973-6247.75997
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and specificities of red cell alloantibodies among blood recipients in the Malaysian state of Kelantan

Abstract: Background:Red blood cell (RBC) alloantibodies may be formed following exposure to RBC antigens. In most cases, the alloimmunization develops during pregnancy or from previous blood transfusions. The RBC antigens and their alloantibodies vary among different human populations and ethnic groups, and they do have a clinical significance for their adverse immunological reactions.Aims:This study aimed at studying the prevalence of RBC alloantibodies at the Blood Transfusion Unit of Hospital Raja Perempuan Zainab I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 15 publications
(14 reference statements)
4
12
3
Order By: Relevance
“…Others have reported the prevalence of anti-Le a to be in the range of 3.68-24.6%[672627] and that of anti-Le b to be between 1.21 and 14.3%,[672728] which is relatively high as compared to our data.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Others have reported the prevalence of anti-Le a to be in the range of 3.68-24.6%[672627] and that of anti-Le b to be between 1.21 and 14.3%,[672728] which is relatively high as compared to our data.…”
Section: Discussioncontrasting
confidence: 70%
“…[2] In our study, 8.22% of detected antibodies were of anti-M specificity and 2.96% were anti-N. Various authors report the prevalence of anti-M to be ranging from 3.6% to 13.8%,[4567] whereas frequency of anti-N is reported to be in the range of 0.87-1.47%. [68] Our study reported majority (84%) of anti-M and 77.78% of anti-N to be of IgG class or possessing an IgG component reacting at 37°C and hence, potentially clinically significant.…”
Section: Discussionmentioning
confidence: 54%
“…The alloimmunization frequency detected in transfused patients was 1.02%. A similar frequency was reported in Malaysia in a group of 5,719 patients, with an overall prevalence of 1.13% [7]. In the Costa Rican population, the frequency was 1.93% [8].…”
Section: Discussionmentioning
confidence: 55%
“…Its prevalence among alloantibodies detected in patients has been reported to range from 3.1 to 17.5 % [3][4][5][6][7][8]. Like most of Rh antibodies, anti-c also belongs to Ig G class of immunoglobulins and is an important cause of hemolytic transfusion reaction, more so in DHTR [9].…”
Section: Discussionmentioning
confidence: 99%